Advance care planning clinic: A structured clinical experience for internal medicine residents. Issue 10 (10th August 2021) - Coyle, Andrew; Bhatia, Sonica; Reyes Arnaldy, Amy; Wang, Katherine; Lindenberger, Elizabeth C.; Fishman, Mary
Abstract: Background: Advance care planning (ACP) is an important step to provide medical care consistent with patients' preferences and values. Nationally, rates of ACP completion are low, and internal medicine residency clinics face additional barriers. To address this need, we implemented an ACP clinic for internal medicine residents. Methods: An ACP clinical experience was created for PGY2 residents beginning in 2018, with 6 total sessions, consisting of consolidated didactics, protected time to identify, outreach, and schedule patients, and two half days of dedicated ACP visits. Residents were surveyed before (end of PGY1) and after (end of PGY2) the intervention. The preceding residency class, serving as a historic control, only received the curriculum and were surveyed at the end of their PGY2 year. Electronic medical record (EMR) data was accessed to track ACP documentation. Results: The overall survey response rate was 124/134 (93%). Comparing the intervention cohort before and after the intervention, there was a significant increase in self‐assessed confidence in completing ACP (2.1/4.0 vs 3.5/4.0, p  < 0.01). Comparing the intervention and historic cohorts (end of PGY2), the intervention was associated with improved confidence in ability to complete ACP for their patients (3.5/4.0 vs 2.7/4.0, p  < 0.01). The historic control had no increase in ACP documentation rates over time, while the intervention cohort had a 13.9% absolute increase in ACP documentation for their patients over the course of residency ( p  < 0.01). Conclusion: The creation of an ACP‐specific clinical experience, in conjunction with existing curricula, resulted in significant improvements in knowledge, self‐assessed skills and behavior, and EMR documentation.